Clinical implication and immunological characterisation of the ARF-GEF family member CYTH4 in ovarian cancer - Qinyi Zhang; Qingying Wang; Sufang Wu; Jiawen Zhang (Taylor & Francis Group, 2020)
Background The GTP exchange factors on ADP-ribosylation factor (ARF) mediate the GDP/GTP exchange on ARF, serve as regulators in protein trafficking and membrane dynamics, and play critical roles in various cell processes. However, the relationship between the expression of ARF-GEF family genes and clinical implications in ovarian cancer remains unclear. Methods We performed a systematic investigation on the role of ARF-GEF family genes in ovarian cancer by using Gene Expression Omnibus (GEO), Kaplan-Meier plotter, Gene set enrichment analysis (GSEA), TIMER and TISIDB database. Results We found that the ARF-GEF family gene CYTH4 exhibited significant expressional upregulation in ovarian cancer compared to normal ovary tissues. The expression of CYTH4 was also higher in metastases from the omentum than in matched primary ovarian tumours. Kaplan-Meier plotter showed that high expression of CYTH4 predicted worse overall survival, progression free survival and post-progression survival of ovarian cancer patients. Notably, from our correlation analysis, CYTH4 expression showed closely association with tumour-infiltrating immune cells. Intriguingly, the expression of CYTH4 was also significantly correlated with a variety of immunomodulators, chemokines and major histocompatibility complex molecules. Conclusion Overall, our findings provide a valuable source of data about the clinical significance of CYTH4 in ovarian cancer.